2019 41st Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2019
DOI: 10.1109/embc.2019.8856776
|View full text |Cite
|
Sign up to set email alerts
|

Gland Segmentation in Histopathology Images Using Deep Networks and Handcrafted Features

Abstract: Histopathology images contain essential information for medical diagnosis and prognosis of cancerous disease. Segmentation of glands in histopathology images is a primary step for analysis and diagnosis of an unhealthy patient. Due to the widespread application and the great success of deep neural networks in intelligent medical diagnosis and histopathology, we propose a modified version of LinkNet for gland segmentation and recognition of malignant cases. We show that using specific handcrafted features such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Stain decomposition is achieved based on an orthonormal transformation of RGB channels. It is shown that the boundaries of glands in the hematoxylin component are more visible [9].…”
Section: A Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…Stain decomposition is achieved based on an orthonormal transformation of RGB channels. It is shown that the boundaries of glands in the hematoxylin component are more visible [9].…”
Section: A Preprocessingmentioning
confidence: 99%
“…For a better representation of the color image information, stain decomposition is used. Rezaei et al [9] propose using handcrafted features and Hematoxylin components as network input. They show that the red channel and the Hematoxylin component have more information for segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…ResNet [55], VGGNet + CNN [56], DBN [57] Analysis of interstitial lung diseases CNN [58] Table 1. Cont.…”
Section: Classificationmentioning
confidence: 99%
“…Popular segmentation-related research areas include nuclei segmentation, tumor segmentation, gland segmentation, etc. An accurate nuclei segmentation can unveil a lot of information about cancer diagnostics [3,9,18] while an accurate gland segmentation or organ segmentation is important to study and obtain morphological statistics like volume and shape for quantitative diagnosis [2,11,15,16,17].…”
Section: Introductionmentioning
confidence: 99%